Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/er.4536
|View full text |Cite
|
Sign up to set email alerts
|

Highly branched poly(arylene ether)/surface functionalized fullerene‐based composite membrane electrolyte for DMFC applications

Abstract: Summary Sulfonated branched polymer membranes have been gaining immense attention as the separator in energy‐related applications especially in fuel cells and flow batteries. Utilization of this branched polymer membranes in direct methanol fuel cell (DMFC) is limited because of large free volume and high methanol permeation. In the present work, sulfonated fullerene is used to improve the methanol barrier property of the highly branched sulfonated poly(ether ether ketone sulfone)s membrane without sacrificing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Compared with the pure CS membrane, the hybrid membranes had a slightly higher initial thermal decomposition temperature with the doping of fillers (UiO‐66‐SCNT and UiO‐66‐SCNT@GO), indicating its good thermal stability. The results of TG demonstrate that the membranes meet the application requirements of PEMFC …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Compared with the pure CS membrane, the hybrid membranes had a slightly higher initial thermal decomposition temperature with the doping of fillers (UiO‐66‐SCNT and UiO‐66‐SCNT@GO), indicating its good thermal stability. The results of TG demonstrate that the membranes meet the application requirements of PEMFC …”
Section: Resultsmentioning
confidence: 77%
“…Direct methanol fuel cell (DMFC) is a polymer electrolyte membrane fuel cell and widely used in portable energy and transportation equipment due to high power density, good switching capability, and low operating temperature . As a key part of DMFCs, the proton‐exchange membrane (PEM) is responsible for the proton transportation to ensure the normal operation of fuel cells .…”
Section: Introductionmentioning
confidence: 99%
“…In particular branched sulfonated polymer prepared with bisphenol fluorine monomer showed excellent stability in Fenton's reagent with outstanding proton conductivity . The performance of the branched polymer membranes can be further improved by mixing with suitable filler …”
Section: Introductionmentioning
confidence: 99%
“…7 The performance of the branched polymer membranes can be further improved by mixing with suitable filler. 9,10 Metal-organic frameworks (MOF) have been used in various fields such as catalysis, separation, adsorption, and drug delivery, etc. [11][12][13][14] Recently, MOFs were utilized as proton conductors in the field of energy material.…”
Section: Introductionmentioning
confidence: 99%
“…In the article by Neelakandan et al, the second affiliation was missing. The corrected affiliations for all authors are shown above.…”
mentioning
confidence: 99%